Who gets what--and why : the new economics of matchmaking and market design - Roth, Alvin E., 1951- (Boston : Houghton Mifflin Harcourt, 2015)
"A Nobel laureate reveals the often surprising rules that govern a vast array of activities -- both mundane and life-changing -- in which money may play little or no role. If you've ever sought a job or hired someone, applied to college or guided your child into a good kindergarten, asked someone out on a date or been asked out, you've participated in a kind of market. Most of the study of economics deals with commodity markets, where the price of a good connects sellers and buyers. But what about other kinds of "goods," like a spot in the Yale freshman class or a position at Google? This is the territory of matching markets, where "sellers" and "buyers" must choose each other, and price isn't the only factor determining who gets what. Alvin E. Roth is one of the world's leading experts on matching markets. He has even designed several of them, including the exchange that places medical students in residencies and the system that increases the number of kidney transplants by better matching donors to patients. In Who Gets What -- And Why, Roth reveals the matching markets hidden around us and shows how to recognize a good match and make smarter, more confident decisions"--
Part I. Markets are everywhere -- Introduction: every market tells a story -- Markets for breakfast and through the day -- Lifesaving changes -- Part II> Thwarted desires: how marketplaces fail -- Too soon -- Too fast: the greed for speed -- Congestion: why thicker needs to be quicker -- Too risky: trust, safety, and simplicity -- Part III. Design inventions to make markets smarter, thicker, and faster -- The match: strong medicine for new doctors -- Back to school -- Signaling -- Part IV. Forbidden markets and free markets -- Repugnant, forbidden... and designed -- Free markets and market design
"An Eamon Dolan book."
Includes bibliographical references (pages 233-246) and index
Keywords: Matching theory; Markets; Game theory; Economics